The role of peer pressure, parental bonding, and sensation seeking in predicting risk-taking attitude among adolescents in Selangor, Malaysia - Binti Hanapi, Nur Nadia; Yaacob, Siti Nor; Daud, Mohd Najmi; Mansor, Mariani (Human Resource Management Academic Research Society, 2023)
Various aspects which are associated with a risk-taking attitude among adolescents have been identified in previous studies. However, the strongest predictor for risk-taking attitude, particularly among adolescents in Selangor, remains elusive. It is essential to identify these factors as the risk-taking attitude which begins in adolescence can lead to a towering of various risky behaviours into adulthood. Therefore, this study aims to investigate the role of peer pressure, maternal and paternal bonding, and sensation seeking in predicting risk-taking attitudes among adolescents in Selangor. Participants (n = 426) consisting of 183 male adolescents (43 %) and 243 female adolescents (57 %) were recruited from 18 secondary schools in Selangor. Attitude towards risk questionnaire (ATTRQ), Peer Pressure, Popularity, Conformity Scale, Parental Bonding Inventory (PBI) and Impulsive Sensation Seeking Inventory (ImpSS) were used for data collection. Multiple regression analyses indicated all variables significantly predict adolescents’ risk-taking attitude. Sensation seeking, peer pressure and paternal bonding were found to be the predictors that lead to adolescent engagement in risk-taking attitudes. Sensation seeking was found to be the strongest predictor. The result may guide relevant agencies and individuals to develop early intervention programs to shape adolescents' healthy psychological development.